STYLISTIC DEVICES IN TRANSLATION - Ibroyimjonova Sitora Ismoil qizi (Research Focus International Scientific Journal, 2024)
. This article demonstrates features of stylistic devices, the difficulties of their translation and some suggested ways of dealing them. Moreover, it indicates the importance of style and the ways of identifying stylistic devices.